2017
DOI: 10.1186/s12912-017-0207-5
|View full text |Cite
|
Sign up to set email alerts
|

Australia’s first transition to professional practice in primary care program for graduate registered nurses: a pilot study

Abstract: BackgroundIncreases in ageing, chronic illness and complex co-morbidities in the Australian population are adding pressure to the primary care nursing workforce. Initiatives to attract and retain nurses are needed to establish a sustainable and skilled future primary care nursing workforce. We implemented a transition to professional practice program in general practice settings for graduate nurses and evaluated graduate nurse competency, the graduate nurse experience and program satisfaction. This study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 14 publications
1
46
0
Order By: Relevance
“…The findings of this study support previous research that general practice employment offers an attractive career option for new graduate nurses Peters et al 2015;Aggar et al 2017;Thomas et al 2018). While some participants indicated an intention to gain future acute care employment, they did not feel that a primary care transition program was a barrier to this.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The findings of this study support previous research that general practice employment offers an attractive career option for new graduate nurses Peters et al 2015;Aggar et al 2017;Thomas et al 2018). While some participants indicated an intention to gain future acute care employment, they did not feel that a primary care transition program was a barrier to this.…”
Section: Discussionsupporting
confidence: 84%
“…New graduate participants emphasised the value they placed on the support provided by their mentors and builds on previous research relating to mentoring in diverse new graduate workplaces Dadiz & Guillet, 2015;McInnes et al 2015b;Tracey and McGowan 2015) (Aggar et al 2017;Bloomfield et al 2018). Studies into mentoring in acute care settings support findings from this study that mentors must be involved in establishing expectations for the mentee, and are provided with support to mentor effectively (Kalischuk et al 2013;Staykova et al 2013).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Based on the results of a self-assessment scale and a knowledge test, Zeinab Abou El-Fotoh, Elmolla, and Abdeen (2016) concluded implementation of a transition programme for new nurses had a positive effect on their "competency skills' performance and knowledge immediately and at three months postprogramme" (p. 225). Aggar, Bloomfield, Thomas, and Gordon (2017) likewise found that that transition to practice programmes facilitated graduate nurse competency and suggested they were a viable health human resource strategy.…”
Section: Introductionmentioning
confidence: 99%
“…With all the challenges that burden NGRNs during transition from student to practising clinician, many recent studies have shown that a transition program provides that added layer of support and guidance that fledgling NGRNs need with clinical decision making and skill development (Aggar, Bloomfield, Thomas, & Gordon, 2017;Ankers et al, 2018;Blevins, 2018;Gazaway et al, 2016;Henderson et al, 2015;Kavanagh & Szweda, 2017;Lea & Cruickshank, 2017;Ortiz, 2016;Patterson, Boyd, & Mnatzaganian, 2017;Voldbjerg et al, 2017;Walton, Lindsay, Hales, & Rook, 2018). These programs have shown to enhance socialisation into the workplace, advance skill development, and reduce uncertainty with the presence of dedicated senior nurses on hand to contact when uncertainty arises (Ankers et al, 2018;Blevins, 2018).…”
Section: Transition Programs and Supportmentioning
confidence: 99%